Hearing loss in patients with mucopolysaccharidoses‐1 and ‐6 after hematopoietic cell transplantation: A longitudinal analysis. Issue 6 (9th July 2020) - van den Broek, Brigitte T. A.; Smit, Adriana L.; Boelens, Jaap Jan; van Hasselt, Peter M.
Abstract: Hearing loss is frequently seen in mucopolysaccharidoses (MPS) patients. Although hematopoietic cell transplantation (HCT) increases overall survival, disease progression is observed in certain tissues. This study describes the course of hearing loss (HL) over time in transplanted MPS patients. Transplanted MPS patients between 2003 and 2018 were included and received yearly audiological evaluation, including auditory brainstem response (ABR) or pure tone audiometry (PTA). Twenty‐eight MPS‐1 and four MPS‐6 patients were analyzed with a median follow‐up of 5 years (range 11 months–16 years). Air conduction threshold improved significantly over time ( P < .001) with a PTA 1‐year post‐HCT of 50 ± 0.7 dB to 23 ± 11 dB 13 years post‐HCT. Bone conduction threshold worsened with a PTA 1 year post‐HCT of 10 ± 7 dB to 18 ± 9 dB 13 years post‐HCT ( P = .34). The degree of HL varied from mainly mild‐severe early after HCT to normal‐mild at longer follow‐up. The type of HL consisted of mainly conductive in the first years post‐HCT in contrast to mainly sensorineural at longer follow‐up. MRIs of the cerebellopontine angle did not show abnormalities. HL is still seen in patients with MPS despite HCT and consists of a conductive type early after HCT in contrast to a sensorineural type at longer follow‐up in the majority of cases. Yearly follow‐up of HL is necessary to timely intervene, as hearing is important in the speech and language development of children and their academic achievements. Abstract :